PENYULUHAN RUMAHKAIDAH TEKNIK - Yulianto Purwono Prihatmaji (Asian Journal of Innovation and Entrepreneurship, 2013)
There are many homes that do not fit the criteria for a healthy home. Besides lackof awareness of citizens to the appropriate criteria for home rule Engineering. So it isless strong even less inhabitable. The purpose of the extension of this technique is ahome rule so that people know what it is home rule technique, how the criteria forhome rule and the benefits of home Mechanical Engineering Rule itself. Methods usedinclude retrieving data in the form of the number of houses in the village head's house,then counseling is done by giving leaflets and briefed the residents about the importanceof home rule Engineering, Mechanical criteria for home rule, the benefits of home ruleEngineering. The results achieved in this program are the citizens know about theimportance of home rule technique, criteria for home health, and the benefitsof homerule technique, and can apply them in their homes.